New Challenges and Threats to The Tourism Industry in The Fighting Against COVID-19 - Inna LEVYTSKA; Alona KLYMCHUK; Valentina POSTOVA; Nataliia KOTSERUBA (Communications of International Proceedings, 2020)
The article is devoted to the study of current problems of development of the tourism industry in the fight against COVID-19. The main trends in the development of the tourism sector are identified, as well as the tools that provide streamlining and regulation of the tourism industry in different countries. The analysis of the state of the tourist industry in the conditions of pandemic spread is carried out. It is proved that the revival of the tourism industry is possible only based on the effective organization of the tourism business by forecasting and eliminating possible risks and dangers that cause significant losses to the industry. The main problems and threats that affect the activities of the tourism business are identified. The reasons for the deterioration of tourism enterprises, the main of which is the inability to adapt to the conditions of doing business in a pandemic. Based on the conducted analysis the threats and dangers which can arise in the course of activity of the tourist enterprises of Ukraine are formed. This approach made it possible to propose stabilization measures that will revive the tourism sector in a pandemic. At the same time, strategic changes in the conditions of coronavirus spread should be quite flexible to changes in the external environment of the tourist enterprise. It is established that ensuring the creation of a high-quality competitive product of the tourism industry is possible due to the training of specialists in the tourism business. Besides, the elimination of shortcomings in the regulatory framework for the regulation of the tourism industry should be a key prerequisite for the effective functioning of tourism businesses at all levels. Based on the conducted researches it is established that revival of tourist activity in the conditions of a pandemic should take place in the direction of strengthening of cooperation with such elements of the infrastructure of hospitable business as tourist agencies, excursion bureaus, insurance companies, trade enterprises, advertising agencies, etc. agencies. It is proved that measures to stabilize the tourism sector in the context of a pandemic must be adapted to new challenges and threats, as well as use effective tools to achieve new opportunities in the field of tourism.
Keywords: tourism industry; international tourism; sphere of tourism; COVID-19; pandemic.